DEVELOPMENT OF CONTEXTUAL ASSESSMENT INSTRUMENTS FOR STUDENTS’ CRITICAL THINKING SKILLS USING KAHOOT QUIZ - Septenia, Erina; Maryani, Maryani; Prastowo, Sri Handono Budi (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the contextual-based instrument of the game assisted by the kahoot quiz to measure students' critical thinking skills. The design in this study is Research and Development with a limited trial on 10 students of class X-Mipa 2 and a broad trial on 30 students of class X-Mipa 5. The data taken in this study are content validation by experts, validity, reliability , level of difficulty, and differentiating power, questionnaires on student responses to the instrument, and tests of critical thinking skills. The results showed that the percentage of appropriateness according to material experts was 93.33% and media experts was 81.05% with very feasible criteria. Student responses to the assessment instrument received a positive response from all students. Critical thinking ability as measured by the instrument got an average score of 64 with good category. Based on the results of the study, it can be said that the contextual-based instrument assisted by the Kahoot quiz is used to measure students' critical thinking skills